4 - Creolising Political Identity and Social Scientific Method - Gordon, Jane Anna (Africa Development, 2021)
Both nurturing and giving institutional expression to a solidarity of diverse people and scholarly communities on the African continent and its transnational diaspora, CODESRIA has embodied the imperative of continuing the unfinished work of building a world that is no longer colonial. But which methods are best suited to such decolonizing work? In what follows, I suggest that the concept of creolization, that emerged to grasp the distinctly African world of the Caribbean, remains an especially useful resource, especially if rearticulated and qualified in the ways for which I advocate.